PENGARUH KESIAPAN BELAJAR TERHADAP HASIL BELAJAR SISWA PELAJARAN EKONOMI XI IPS SMAS MUJAHIDIN PONTIANAK - Yanti, Weli; Mashudi, Mashudi; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to know the influence of learning readiness on the learning achievement students in the economic subject in the class XI IPS SMAS Mujahidin Pontianak. The writer conducted quantitative descriptive method which study relation. The writer collected the data by using direct and indirect communicating, observation and documentation. Technique the tools was used in this research were questionnaire, observation guide, interview guide, and documentation. The sampel of this research was the 83 students of XI IPS SMAS Mujahidin Pontianak. The result of this research showed that there were positive influence of learning readiness on the learning achievement which showed by correlation coefision 0,327. The coefision determination in this research the influense of independent variable (X) which learning readiness on the dependent variable (Y) which learning achievement 0,107or 10,7%. Meanwhile the rest was influence the other variable which not explained in this research the calculation of simple linear regretion equality Y= 31,775 + 0,634X, which means a constant value of 31,775 if leaning readiness is zero (0), then learning readiness is equal to 0,634. Which meant the constant 0,634 the variable regression coefision of readiness in the learning which 0,634, this means that an increase in learning readiness is a equal to one (1) then the learning achievement will increase as 0,634.Keywords: Readiness Learning, Learning Achievement